Analysis of CO2 transmission in a micro direct methanol fuel cell. (1st April 2015) - Yuan, Zhenyu; Yang, Jie; Li, Zipeng; Sun, Yuge; Ye, Ning; Shen, Hongyuan
Abstract: In this paper, the behavior of CO2 transmission in a micro direct methanol fuel cell (μDMFC) is investigated through both simulations and experiments. A model is built to describe the change of CO2 volume fraction in the anode channel under different operation parameters (e.g., current density, flow rate and operation temperature). In addition, the dynamic movement of a single CO2 bubble is also simulated to study the CO2 characteristics. Furthermore, a metal-based transparent μDMFC with the active area of 0.8 cm × 0.8 cm is designed and fabricated to evaluate the two-phase flow characteristic as well as the corresponding cell performance. Experimental results reveal that the operating current, the flow rate and the temperature can significantly influence the quantity and shape of CO2 bubbles: 1) small discrete bubbles can grow up to a gas column with the increase of operating current; 2) the amount and the size of CO2 bubbles will decrease with the increase of the flow rate; 3) higher operating temperature will prompt the size of CO2 bubbles. The experimental results are well in agreement with the simulation. Highlights: The distribution of CO2 volume fraction is modeled. The dynamic movement of a single bubble is simulated. A metal-based μDMFC with 0.64 cm 2 is fabricated. The experimental results are well in agreement with the simulation.